KONDISI SOSIAL EKONOMI MASYARAKAT INDONESIA PADA MASA TANAM PAKSA (1830-1870) - Romadi, - (Faculty of Social Science, Universitas Negeri Semarang, 2011)
After Napoleon’s defeat in the Coalition War in Europe, parts of Indonesia which was originally colonized by the British returned to the Netherlands in 1817. Although the Netherlands applied a change in the politics of colonization, but still comes up a lot of Inodesian’s resistance. Among the resistances are Pattimura Resistance in the Moluccas (1817), Imam Bonjol in Minangkabau (1821-1833), Prince Diponegoro in Java (1825-1830) and so on. As a result of the resistance, Dutch spent lot to put it down. Besides, the political upheaval that occurred in Europe and the Dutch efforts to build its level equal with other European countries led the Dutch to politics that is able to exploit the wealth of Indonesian earth quickly. Among the political measures adopted is Forced Planting. This paper presented in a descriptive analytical model attempts to bring back a picture of Indonesian society during the cultivation, based on historical literature sources. Keywords: economic, social, the forced planting (Tanam Paksa)